ANALYSIS THE VIOLATION OF MAXIM IN VLOG JURNALRISA EPISODE “TANYARISA #11 – SPECIAL PETER CS” - Nikita Febriyani; Cynantia Rachmijati (PROJECT (Professional Journal of English Education), 2021)
Abstract The aims of this research to analyze the violation of maxim on vlog jurnalrisa the episode “Tanyarisa #11 - SPESIAL PETER CS”. To achieve this goal, this study was designed with descriptive qualitative. Data collected by transcription Host and Speaker conversations (childhood friends) in Youtube Channel jurnalrisa with a duration of 50:36 minutes. The data is then analyzed by four Grice maxims quantitatively. The finding shows; first, there are three types of a maxim of violations as 50% violated the maxim of quantity, 40% violated the maxim of relevance, 10% violated the maxim of manner. Second, the dominant type of violation that has been violated of quantity because they tend not to reveal information. Third, the violations of the maxim happen because when the speakers provide information or utterances to change the conversation, there is ambiguity, obscurity answers, and exaggerates or reduces information so it is not informative. Keywords:        Cooperative Principle, Violation of maxim, vlog